Shamba showdown play test session 1 - Kigo, Samm; Odera, Denis; Girvetz, Evan; Chilambe, Pedro; Waswa, Boaz (2023)
Report summarizing the findings from the first play test session of the Shamba Showdown Game, held at Murang’a University on May 10, 2023